Quasi-far-field blast responses of hierarchical orthogrid-stiffened sheet molding compound (SMC) protective door structures. (1st August 2018) - Zhao, Zheng; Zhang, Bei; Zhou, Jiannan; Chen, Hailong; Wang, Bo; Zhou, Yinzhi; Xu, Ying; Jin, Fengnian; Fan, Hualin
Highlights: Hierarchical orthogrid stiffened structure is used to design and make protective door. Blast responses of the door are revealed by experiments and FEM. Hierarchical stiffened structure greatly improves the anti-blast capability of the door. SMC material greatly reduces the weight of the protective door. Abstract: To make protective door structure light, sheet molding compound (SMC) material was adopted to make all-composite blast-resistant door through hot-pressing method. To make the door panel have enough bending rigidity, two-scale orthogrid structures are designed to stiffen the SMC panel. The 1 st order primary orthogrid enhances the integral bending rigidity of the door and makes the door stiff and strong enough under specific blast loading. The 2 nd order orthogrid is much thinner but denser and is used to stiffen the mono-cell panel encased by the 1 st order orthogrid to resist local failure under explosion. Experiments were carried out to reveal the tensile property of the SMC material and the blast responses of the SMC protective doors. Under required over-pressure, the composite door has satisfied anti-blast performance. The maximum deflection is close to 3 mm, but the panel completely rebounds back leaving little residual deformation. Finite element modeling (FEM) was applied to investigate and compare the dynamic responses of door panels with different stiffening styles. It is found that the 1 st order orthogrid controls the dynamic response of the door and setting up a transverse primary rib at the central cross section will make the door stiffer and stronger. The research validates that the SMC door satisfies the requirement of blast resistance and is a lightweight candidate for traditional steel or concrete protective door structures.